2022
DOI: 10.3390/fermentation8020069
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Volatile Compounds and Quality Characteristics of Salted Shrimp Paste Stored in Different Packaging Containers

Abstract: Quality changes of salted shrimp paste, one of the most popular traditional Thai fermented food ingredients, stored in different packaging containers including polypropylene containers (PP), polyethylene terephthalate containers (PET), glass jar containers (GJ) as well as LLDPE/Nylon vacuum bags (VB) at room temperature (28 ± 1 °C) for 15 months were studied. The relationship between quality attributes (i.e., volatiles, browning index (A420), biogenic amines, TBARS) and consumer acceptability as indicated by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The results indicated that lipid oxidation occurred at the highest level in the breast cuts, compared to the others, corresponding well with the highest UFA found in this sample. However, various studies identified values of 2-2.25 mg MDA/kg per sample as the recognized limit for no rancidity in meat and meat products [2,4,15]. As a consequence, the TBARS value in all the goat primal cuts ranged from 0.20 to 0.35 mg MDA/kg per sample, which did not exceed the approved limit value.…”
Section: Lipid Oxidation Productsmentioning
confidence: 97%
See 1 more Smart Citation
“…The results indicated that lipid oxidation occurred at the highest level in the breast cuts, compared to the others, corresponding well with the highest UFA found in this sample. However, various studies identified values of 2-2.25 mg MDA/kg per sample as the recognized limit for no rancidity in meat and meat products [2,4,15]. As a consequence, the TBARS value in all the goat primal cuts ranged from 0.20 to 0.35 mg MDA/kg per sample, which did not exceed the approved limit value.…”
Section: Lipid Oxidation Productsmentioning
confidence: 97%
“…Lipid (0.1 g) was dissolved in 5.0 mL of isooctane and subjected to absorbance measurement at 234 nm using a UV-1601 spectrophotometer (Shimadzu, Japan). Peroxide value (PV) and thiobarbituric acid reactive substances (TBARS) value were measured [15]. For PV measurement, cumene hydroperoxide (0.5-2 ppm) was used for a standard curve (y = 0.5603X + 0.1724, R 2 = 0.9858) and the results were expressed as mg hydroperoxide/kg sample.…”
Section: Measurement Of Lipid Oxidation Products (Cd Pv Tbars)mentioning
confidence: 99%
“…The shrimp paste samples were diluted in peptone water containing 0.85% NaCl in serial tenfold steps prior to application onto agar by the spread plate technique and followed by incubation. The total viable count was analyzed using a standard plate count agar (pH 7.5) according to Bacteriological Analytical Manual (BAM) as previously described (18). The lactic acid bacteria count was performed using De Man-Rogosa-Sharpe (MRS) agar (19).…”
Section: Microbial Load Analysismentioning
confidence: 99%
“…Previous studies (Yunilas et al 2019;Wang et al 2022;Baena et al 2022) emphasized that interactions among substrates, incubation periods, and the types and quantities of enzymes influence the degradation of crude fibers. The fermentation rate significantly affects enzymes produced in the medium (Pongsetkul et al 2022).…”
Section: Proximate Composition Of Fermented Rain Tree Seed Mealmentioning
confidence: 99%